Pengembangan Metode Identifikasi Kerusakan DNA Spermatozoa Ternak - Teguh Ari Prabowo; R. Iis Arifiantini; Dondin Sajuthi; Uus Saefullah (Jurnal Sain Veteriner, 2016)
The success of artificial insemination is very much determined by the quality of spermatozoa. The detection or identification of damaged chromatin of spermatozoa DNA is very important to forsee the adverse clinical outcome. However, the method of identification is still depended on expensive imported kits. Therefore, the objective of this research was to developed an identification kit to determine the quality of livestock spermatozoa DNA chromatin.This study consist of three step. Step 1) Determination of low melting point agarose (LMP-agarose) concentration which is 0,6%, 0,7% and 0,8%. 2) Comparison of three lysis solution (LS) which is LS I (0.4M Tris, 0.8M DTT, 1% SDS, pH 7.5), LS II (0.4M Tris,2 M NaCl, 1% SDS , pH 7.5), and LS III (0.4M Tris-HCl, 2M NaCl, 1% SDS 0,05 M EDTA, pH 7.5). 3) Comparison different staining which is Eosin yellow and Methylene blue. The results showed that 0.6% LMP-agarose demonstrated the best concentration to “trapped the spermatozoa” compared for sheep and goats. whereas the three concentration of spermatozoa cows can not be used to trap spermatozoa cow. The best formulation to lysis the membrane was LS III (0.4M Tris -HCl, 2M NaCl, 1% SDS 0,05 M EDTA). The best staining was eosin yellow and methylene blue with 2:1 ratio.